HIGH PERFORMANCE WORK SYSTEMS AND BUMDES EMPLOYEE PERFORMANCE: THE ROLE OF AMBIDEXTERITY AND LEADERSHIP AS KEY VARIABLES - Ahmad (The Asia Pacific Journal Of Management Studies, 2025)
The purpose of this study is to explore the mediation model moderated by ambidextrous leadership and employee ambidexterity in the relationship between high-performance work systems and employee performance. A census approach was used to collect data from the target employees. Therefore, using a cross-sectional design, 387 employees representing tourism sector BUMDes in Banten Province participated in this study. Structural equation modelling with the help of SPSS plus AMOS was used to analyse the proposed hypotheses. By integrating social exchange theory and the AMO model, the results show that ambidextrous leadership moderates the relationship between high-performance work systems and employee ambidexterity. At high levels of ambidextrous leadership, the relationship between high-performance work systems and employee ambidexterity becomes stronger. Furthermore, ambidextrous leadership moderates the indirect effect of employee ambidexterity in the relationship between high-performance work systems and employee performance. This research yields additional understanding of the critical role of ambidextrous leadership in unlocking the opportunities and strengths between HPWS and employee performance.